PAPILLARY RENAL CELL CARCINOMA AS AN ABDOMINAL CYSTIC MASS - Khan, Osama Sherjeel; Muhammad Yunas; Nadeem Ijaz; Sidrah Iftikhar; Toru, Hamza Khan (Journal of Ayub Medical College Abbottabad, 2022)
Papillary renal cell carcinoma comprises around 15% of all renal cell carcinomas. Patients are usually asymptomatic, and 25 percent of individuals have advanced locoregional disease at presentation. Papillary renal cell carcinoma presenting as a huge abdominal cystic mass is uncommon and is reported rarely in literature. We present a case of renal cell carcinoma presenting with abdominal pain, distention, and constipation. A retroperitoneal cystic lesion measuring 23.4Ã—23.8 cm cyst was reported on ultrasonography as potential cause of the symptoms. We now talk about the case of a 57-year-old male who presented to us with abdominal pain, distension, and constipation. He also had a history of on and off low-grade fever for the last seven months. A computed topography (CT scan) of the abdomen and pelvis with intravenous and oral contrast revealed a large retroperitoneal cystic mass extending from the left hypochondrium to the left kidney and into the pelvis crossing the midline. Internal calcific foci, enhancing septa, irregularly thickened walls and hyperdense nodules were also demonstrated. A radical left nephrectomy via a midline laparotomy was performed electively. The cystic mass was excised and the specimen was sent for histopathological evaluation which revealed papillary renal cell carcinoma with PAX-8 and CK-7 positivity. Patient made an uneventful recovery post-operatively and was discharged. Cystic tumors of renal origin can rarely present as a huge abdominal cystic mass confusing them for masses of intestinal or hepatic origin. Timely diagnosis can be made with a detailed history, examination, imaging studies and histopathology, and instigate timely intervention.